Biology and Ecology of Blood Plasmodia - Mirzaliev Abdujabbor Mamatyusuf ugli (Scholars Digest Publishing, 2023)
This article information about focused on the biology and ecological characteristics of blood plasmodia, which dolizarb is becoming a problem these days. This article provides information about the diseases caused by the proliferation of blood plasmodia. Also, this article can provide information for young researchers and the general public on how to avoid these organisms and the various diseases they cause.
Keywords: Plasmodium, spores, erythrocyte, malaria, merozoite, Anopheles, V. calacaratus.